Severity and immediate neurodevelopmental outcome in term neonates with hypoxic-ischemic encephalopathy admitted in NICU at a tertiary hospital in Bangladesh - Debnath, Bithi; Khan, Naila Zaman; Mahfuz, Rumana; Mollah, Abid Hossain (Bangladesh Critical Care Journal, 2021)
Background: Neonatal hypoxic ischemic encephalopathy (HIE) is a major cause of mortality, morbidity and long-term neurological deficits. Objective: The aim of the study was to determine the severity of encephalopathy and immediate neurodevelopmental outcomes in term neonates with HIE admitted in NICU at a tertiary care hospital. Materials and Methods: This was a Prospective Cohort study conducted between July 2016 and June 2017 at Dhaka Medical college Hospital, Dhaka. Asphyxiated term newborns who came within 12 hours of birth were enrolled in this study. Sarnat and Sarnat score was used to assess newborns immediately after birth to classify HIE. Neurodevelopmental assessment was performed using age specific rapid neurodevelopmental assessment tool (RNDA) at and 3 months after discharge to identify impairment in specific developmental domains. We determined the relation between severity of HIE and clinical outcome. Results: 60 patients were included in this study and their mean duration of hospital stay was 7.19 ± 5.26 days. The majority, 40% had moderate HIE, followed by 33.33%, 26.67% that had mild and severe HIE respectively. A total of 20% died, and most of them had severe HIE (83.33%). Normal development was found in only 11.67% cases. Moderate and severe neurodevelopmental impairment (NDI) was found in 33.33% and 25% cases respectively. At discharge, the most severely impaired domains were speech, seizure, primitive reflex and behaviour whereas at 3 months of age it was gross motor and seizure. When neurodevelopmental outcome was compared with different stages of encephalopathy, significant association was found between moderate to severe impairment/death with stage III of HIE. Conclusion: Apart from mortality, a significant proportion of term neonates with HIE developed NDIs and adverse neurodevelopmental outcomes was significantly associated with severity of encephalopathy. Bangladesh Crit Care J March 2021; 9(1): 22-27